Legalitas Pernikahan Dini Melalui Dispensasi Kawin Pengadilan Agama Di Kalimantan Selatan - Zaidah, Yusna; al-Amruzi, Muhammad Fahmi; Hafidzi, Anwar (VARIA HUKUM, 2023)
Abstract The high number of early weddings in South Kalimantan, including both hand-arranged marriages and those performed formally with court-provided marriage dispensation services, is the subject of this study. to more thoroughly investigate the legal factors that South Kalimantan religious court judges take into account while handling cases of marriage dispensation. This study attempts to address the issue of early marriage in relation to the court's ability to grant dispensation from marriage as a requirement for legalizing marriage for those who have not reached the legal marriageable age through a constitutional approach, legal sociology, and legal anthropology. The review revealed that the majority of the dispensation petitions submitted had been approved. The judge uses procedural and substantive factors based on laws and regulations to decide the marriage dispensation case, taking into account the facts of the case while also paying attention to the fiqh and the guiding principles of Islamic law, which are derived from the verses of the Koran and hadith. Although there is a perception that judges are quick to grant requests or are thought to play a role in South Kalimantan's legalization of early marriage. Abstrak Fokus kajian ini adalah mengenai tingginya pernikahan dini di Kalimantan Selatan baik yang dilakukan dibawah tangan maupun yang dilakukan scara resmi dengan fasilitas dispensasi kawin dari pengadilan. Untuk selanjutnya menelaah secara mendalam pertimbangan hukum hakim Pengadilan Agama di Kalimantan Selatan dalam memproses perkara dispensasi Kawin. Melalui pendekatan konstitusional dan pendekatan sosiologi hukum dan antropologi hukum penelitian ini Â mencoba menjawab persoalan pernikahan dini dikaitkan dengan kewenangan pengadilan dalam memberikan dispensasi kawin sebagai syarat untuk melegalkan perkawinan bagiÂ  mereka yang belum mencapai usia minimal kawin. Dari telaah yang dilakukan mendapatkan temuan bahwa sebagian besar permohonan dispensasi yang diajukan adalah dikabulkan. Hakim dalam memutus perkara dispensasi kawin didasarkan kepada fakta persidangan dengan menggunakan pertimbangan prosedural dan substansial yang di dasarkan peraturan perundangan dengan tetap memperhatikan prinsip Hukum Islam yang bersumber dari ayat ayat al Quran dan hadis serta kaidah kaidah fikih. Walaupun ada kesan hakim begitu gampang mengabulkan permohonan atau dianggap ikut terlibat dalam legalitas pernikahan dini di Kalimantan Selatan.